THE IMPACT OF LEARNING ON SPORTIVITY ATTITUDE - Akhmad Sobarna; Rony Mohamad Rizal; Sumbara Hambali; Henry Asmara; Denok Suharni (Cakrawala Pedagogik, 2022)
Physical education learning is one of the places or containers to develop and apply good and positive behaviors that are sportsmanship attitudes. This research aims to find out if there is an influence in physical education learning on students' sportsmanship. This research uses quantitative descriptive methods with ex post facto design and this research instrument in the form of questionnaires/questionnaires of sportsmanship attitude, this research was conducted at SMA PGRI 1 Bandung. The sampling technique in this study used Cluster Random sampling with a population of 5 classes with a total of 150 students and a sample of 30 people. Analysis of research data uses a percentage descriptive data analysis. The results showed that the impact of penjas learning on sportsmanship on students was on most criteria with a percentage result of 86.48%. Thus it can be concluded that the impact of penjas learning on the attitude of sportsmanship is on the criteria of most.